2017
DOI: 10.1371/journal.pone.0170272
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Fluid/Intracellular Fluid Volume Ratio as a Novel Risk Indicator for All-Cause Mortality and Cardiovascular Disease in Hemodialysis Patients

Abstract: BackgroundIn hemodialysis patients, fluid overload and malnutrition are accompanied by extracellular fluid (ECF) expansion and intracellular fluid (ICF) depletion, respectively. We investigated the relationship between ECF/ICF ratio (as an integrated marker reflecting both fluid overload and malnutrition) and survival and cardiovascular disease (CVD) in the context of malnutrition-inflammation-arteriosclerosis (MIA) complex.MethodsSeventy-seven patients from a single hemodialysis unit were prospectively enroll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
81
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(86 citation statements)
references
References 28 publications
2
81
2
1
Order By: Relevance
“…Compared to the l‐BNP group, the h‐BNP group had less muscle strength, lower body weight, lower lean tissue index and lower levels of hemoglobin and albumin, but higher CRP levels. These findings indicate malnutrition and inflammation, which have been associated with overhydration . However, although the h‐BNP group had higher CRP levels, we were not able to confirm the association between overhydration and IL‐6 and TNF‐alpha or any other inflammatory markers, which has been found in studies with larger samples …”
Section: Discussioncontrasting
confidence: 84%
“…Compared to the l‐BNP group, the h‐BNP group had less muscle strength, lower body weight, lower lean tissue index and lower levels of hemoglobin and albumin, but higher CRP levels. These findings indicate malnutrition and inflammation, which have been associated with overhydration . However, although the h‐BNP group had higher CRP levels, we were not able to confirm the association between overhydration and IL‐6 and TNF‐alpha or any other inflammatory markers, which has been found in studies with larger samples …”
Section: Discussioncontrasting
confidence: 84%
“…In this respect, it should be noted that ECV/TBW ratio, which is also often used in the assessment of fluid status, may also be influenced by a reduction in body cell mass leading to a reduction in intra-cellular volume [37]. We also observed lower levels of lean tissue mass and serum albumin levels in patients with more advanced FO [2].…”
Section: Non-cardiovascular Factors On Abnormalities In Fluid Statussupporting
confidence: 51%
“…In this same study, an association between FO and other markers of inflammation, namely, endotoxin and C-reactive protein (CRP) was also found [21]. The association between CRP as a marker of inflammation and FO was further confirmed in a study of 59 PD patients [19] and in a single-center study, using segmental BIA, in CKD patients [22]. A larger study, performed by Hung et al [23] showed significant associations between IL-6 as well as tumor necrosis factor alpha with the OH:ECW ratio in 338 CKD patients.…”
Section: Evidence For the Relation Between Fo And Inflammationmentioning
confidence: 75%
“…The increased mortality risk appears to persist, albeit to a lesser degree, even after the resolution of both risk factors during a subsequent 3 months follow-up period (HR 3.28 with resolution of both risk factors, as compared to a HR of 9.44 with persistent presence of inflammation and FO) [10]. Interestingly, these results are contradicted by another study in which the ECW:ICW ratio, assessed by segmental BIA, nullified the effects of CRP on outcome [22]. However, this ratio is a combined marker of FO and/or malnutrition, given the fact that a loss of LTM may be reflected by a reduction of ICW.…”
Section: Combined Effects Of Fo and Inflammation On Outcomementioning
confidence: 99%
See 1 more Smart Citation